Artificial Synapses: Photoelectric Plasticity in Oxide Thin Film Transistors with Tunable Synaptic Functions (Adv. Electron. Mater. 12/2018). (10th December 2018) - Wu, Quantan; Wang, Jiawei; Cao, Jingchen; Lu, Congyan; Yang, Guanhua; Shi, Xuewen; Chuai, Xichen; Gong, Yuxin; Su, Yue; Zhao, Ying; Lu, Nianduan; Geng, Di; et al.
Abstract : In article number1800556, Hong Wang, Ling Li and co‐workers successfully emulate versatile functions of a biological synapse based on indium–gallium–zinc oxide (IGZO) thin film transistors through a new design by combining photonic and electric stimuli. Meanwhile, the synaptic functions can be mediated by modulating the composition ratio of IGZO film. The work contributes to the development of neuromorphic electronics and the combination of photonics and electric has great prospects in optoelectronic applications.